2015
DOI: 10.1007/s11356-015-4963-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cr(VI) in soil samples from a contaminated area in northern Italy by isotope dilution mass spectrometry

Abstract: The aims of the work were to detect and quantify hexavalent chromium in 14 soil samples from an area in Lombardia (northern Italy) contaminated by two polluted water plumes. Cr(VI) was extracted from the solid samples by applying focused microwaves in an alkaline medium after Cr(III) complexation with EDTA. Cr(VI) was reduced to Cr(III) when previously reported extraction conditions for the analysis of certified reference materials were used, and Cr(VI) could not be reliably quantified in the soil samples. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
0
18
1
Order By: Relevance
“…Probably, when the air-dry soil was wetted with water and extracted in an alkaline solution, iron (II/III)-bearing minerals were solubilized and were capable of reducing Cr(VI) to Cr(III). The capability of Fe(II) to reduce Cr(VI) in a solution over a pH range 2–10 and correlation between reduction of Cr(VI) and the presence of iron in extract of soil was reported by Guidotti et al [37]. Hence, the formed Cr(III) was associated with Fe(III)-hydroxide forming Cr(III)-Fe(III)-precipitate, and removed from the extract during the filtration step.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Probably, when the air-dry soil was wetted with water and extracted in an alkaline solution, iron (II/III)-bearing minerals were solubilized and were capable of reducing Cr(VI) to Cr(III). The capability of Fe(II) to reduce Cr(VI) in a solution over a pH range 2–10 and correlation between reduction of Cr(VI) and the presence of iron in extract of soil was reported by Guidotti et al [37]. Hence, the formed Cr(III) was associated with Fe(III)-hydroxide forming Cr(III)-Fe(III)-precipitate, and removed from the extract during the filtration step.…”
Section: Resultsmentioning
confidence: 85%
“…Considering the reactions which could take place in the alkaline extract, the reduction of Cr(VI) to Cr(III) in the presence of humic substances, solubilised in an alkaline solution (pH about 9.5), is not excluded. Such a process may be facilitated in the presence of soluble Fe(III), which first can be reduced to Fe(II) by humic substances and then oxidized by Cr(VI) in a redox cycle [37]. The high content of Fe found in the extract of organic soil spiked with BaCrO 4 (mass fraction of Fe = 5.7 ± 0.3 mg g −1 , n = 3) indicates that Fe may induce the reduction of Cr(VI).…”
Section: Resultsmentioning
confidence: 99%
“…Single-spike isotope dilution mass spectrometry (IDMS) has also been explored, where samples are spiked with only one isotope corresponding to the species of interest. Guidotti et al demonstrated reliable extraction and quantification of Cr(VI) in contaminated soils using Cr(VI) and ethylenediaminetetraacetic acid (EDTA) extraction, with minimal reduction of Cr(VI) even in soils with high Fe and organic matter content (Guidotti, Abad, Rodríguez-González, Alonso, & Beone, 2015).…”
Section: On-line Analytical Techniquesmentioning
confidence: 99%
“…Isotope dilution mass spectrometry (IDMS) is a calibration technique able to accurately quantify Cr(VI) from soil samples. When multiple spiking is applied Cr(III)-Cr(VI) redox interconversions during sample preparation can be corrected for (Fabregat-Cabello et al, 2012;Garcia Alonso and Rodriguez-Gonzalez, 2013;Guidotti et al, 2015;Rahman et al, 2005). The analytical procedure, standardised by USEPA as method 6800 (USEPA, 2007) requires the addition of known amounts of isotopically enriched Cr(III) and Cr(VI) to the samples before extraction.…”
Section: Introductionmentioning
confidence: 99%
“…preventing its oxidation to Cr(VI) throughout the analytical procedure; ii) it facilitates the extraction of Cr(VI) from the solid sample by complexation of other metals (e.g., Ba, Pb, Sr, Zn) forming insoluble chromates (Fabregat-Cabello et al, 2012;Guidotti et al, 2015). Therefore, since EDTA was able to prevent Cr(III) oxidation to Cr(VI) during extraction, the use of a single isotopicallylabelled Cr(VI)-spike provides an accurate quantification of Cr(VI) in soil by IDMS (Fabregat-Cabello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%